SYNTHESIS, CHARACTERIZATION, MOLECULAR DOCKING, AND ANTICANCER ACTIVITY OF NEW FORMAZAN DERIVATIVES - Ghani, Abdulsattar Hashim A.; Mohammed, Moayed Nemma; Kadhim, Muqdad Irhaeem (PT. Antis International Publisher, 2025)
Objective: This work includes novel formazan compounds containing 5-diazenyl-2-hydroxybenzoic acid with different Schiff bases. SB1 ( N-(6-methoxybenzo[d]thiazol-2-yl)-1-(4-(pyridin-2-yl)phenyl)methanimine), SB2 ( dimethylene(4-((4-(pyridin-2-yl)benzylidene)amino)phenyl)-l6-sulfanamine), SB3 4-(((4-methoxy-6-methyl-1,3,5-triazin-2-yl)imino)methyl)-N,N-dimethylaniline) and SB4 ( 4-(((4-methoxy-6-methyl-1,3,5-triazin-2-yl)imino)methyl)benzene-1,3-diol) leads to formation F1 ( 2-hydroxy-5-((((6-methoxybenzo[d]thiazol-2-yl)imino)(4-(pyridin-2-yl)phenyl)methyl)diazenyl)benzoic acid), F2 ( 5-((((4-(aminodimethylene-l6-sulfaneyl)phenyl)imino)(4-(pyridin-2-yl)phenyl)methyl)diazenyl)-2-hydroxybenzoic acid), F3 (5-(((4-(dimethylamino)phenyl)((4-methoxy-6-methyl-1,3,5-triazin-2-yl)imino)methyl)diazenyl)-2-hydroxybenzoic acid) and F4 ( 5-(((2,4-dihydroxyphenyl)((4-methoxy-6-methyl-1,3,5-triazin-2-yl)imino)methyl)diazenyl)-2-hydroxybenzoic acid) in order. Method: They have been synthesized by the addition reaction of the diazonium salts of 5-diazenyl-2-hydroxybenzoic acid with Schiff bases, and they were designed, synthesized, and confirmed by elemental analyses, FT-IR, 1H-NMR and 13C-NMR spectral data. It noticed the molecular docking results for the interaction of the tested ligands (F1, F2, F3, F4) with the 1T49 protein (PTP1B) reveal several important insights regarding their binding affinities, stability of poses, and interaction profiles within the active site of the enzyme. Results: This suggests that F1 is the best candidate for further development as a potential PTP1B inhibitor, especially in relation to treatment for the breast cancer. All these results are consistent with what this work has reached when conducting an anti-cancer test. This work has investigated the cytotoxic potential of F1 against cell line MCF-7 (breast cancer). Results showed that the compound exhibited significant cytotoxicity toward MCF-7 cells, with an IC₅₀ of 147.6 µg/mL. These findings suggest a selective antiproliferative effect of the compound on cancerous cells compared to normal cells, highlighting its potential as a promising candidate for further anticancer drug development targeting breast cancer. Novelty: This work includes novel formazan compounds containing 5-diazenyl-2-hydroxybenzoic acid with different Schiff bases.